THE CARE OF NURSING TO THE FAMILY: A BIBLIOGRAPHICAL STUDY - Klever Souza Silva; João Batista Tavares; Claci Fátima Weirich (Universidade Federal de Goias, 2004)
The objective of this study was to identify the scientific article about the care of nursing to the family,published in periodic of Brazilian nursing, index-linked article survey to the LILACS, in the period of 1993 the 2003,and to analyze them how much to the concept and composition of the families, systematization and proposals ofaction of nursing and formation and qualification of the authors. In the results we find in 10 years (1993-2003), 9publications concerning nursing in family. Where we can find the predominance of works that focus thesystematization and proposals of action, evidencing of a general form, a lack of studies in the area of nursing infamily, where the Program of Health of the Family appears as principal source of promotion of care of nursing tothe family and motivation for studies that approach this thematic one. All research had had as authorship nursesdoctors, masters and specialists, which acted as professors.